A flame retardant lithium battery positive electrode adhesive and preparation method thereof
The microcapsule adhesive wrapped with flame retardant is prepared by esterified solvent-philic chain segments and reversible addition fracture chain transfer polymerization technology, which solves the problem of thermal runaway of lithium batteries and flame retardant affecting battery performance at high temperatures, and achieves the effect of efficient flame retardant and improving battery circulation performance.
Patent Information
- Application Number
- CN202310147504.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-08
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-02-08
AI Technical Summary
When existing lithium batteries get thermally out of control at high temperatures, the safety valve is delayed to open, resulting in battery damage or safety accidents. The existing flame retardant will affect battery performance when freely free in the battery.
Microcapsule adhesives wrapped with flame retardant are prepared by esterified solvent-philic chain segments and reversible addition fracture chain transfer polymerization technology. The flame retardant is released through high-temperature cracking and complex with high-valent metal ions to prevent reaction with the electrolyte.
Effective flame retardant at high temperatures, improve the conventional circulation performance of the battery, reduce internal resistance, reduce processing costs, and achieve better adhesive and buffering effects through single-layer coating.
Smart Images

Figure BDA0004089653410000091 
Figure HDA0004089653420000011 
Figure HDA0004089653420000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium battery adhesives, and in particular to a flame retardant lithium battery positive electrode adhesive and a preparation method thereof. Background Art
[0002] Among energy storage carriers, lithium-ion batteries of secondary batteries (rechargeable batteries) play an important role. + The battery is embedded and de-embedded back and forth between the two electrodes, which is vividly called a "rocking chair battery". It has the characteristics of high average discharge voltage, high specific energy, high energy density, low self-discharge rate, long cycle life, clean and pollution-free, light weight, small size, and no memory effect. With the rapid development of the lithium battery industry, the performance requirements of lithium batteries have gradually increased. In recent years, safety accidents of power batteries in lithium batteries have occurred from time to time, and the public has gradually paid attention to the safety performance of power batteries. Due to the high energy density of power batteries, during use, the influence of the outside world (such as overcharging, puncture, collision, etc.) will induce the internal temperature of the battery to rise, resulting in thermal runaway of the battery. To solve this problem, the power battery will be equipped with a safety valve. The original intention of the design is that when the internal pressure is too large, the safety valve will open to release the internal pressure of the battery. However, in actual use. The safety valve often cannot be opened in the first time, resulting in a delay in the activation of safety measures, which will cause damage to the battery and even cause safety accidents. In the existing public technology, there are the following schemes to improve safety performance: ① Add high flash point solvents (one or more of fluorinated solvents, sulfone solvents, and cyclic carboxylic acid esters). However, these substances will affect the film formation on the surface of the negative electrode, thereby affecting the cycle performance of the battery; ② Add flame retardants (trimethyl phosphate, triphenyl phosphate, etc.) to improve safety performance. However, if the phosphoric acid-based flame retardant is free in the battery, it will peel off the graphite negative electrode and react with the lithium-intercalated graphite, thereby affecting the battery performance. Recently, polyimide materials have also been used for flame retardancy to achieve better safety performance, but the cost is expensive and not conducive to industrial development.
[0003] In order to avoid the negative impact of flame retardants on graphite negative electrodes when they are free in the battery, for example, Chinese invention patent CN105742733A discloses a method for enhancing the safety of lithium-ion batteries, including the following steps: preparation of microcapsules, the microcapsules include a capsule core part and a capsule shell part, the capsule core part is wrapped inside the capsule shell part, the capsule core part is a flame retardant for lithium ions, and the flame retardant is wrapped inside the capsule shell part to form a microcapsule; the microcapsules are mixed into a solution containing a separator protective agent; the solution mixed with microcapsules is evenly coated on the surface of the separator, and used as a lithium-ion battery separator after drying; the treated separator is assembled and applied to lithium-ion batteries by winding or lamination. Wrapping the flame retardant in the microcapsule and fixing it on the surface of the separator does not affect the viscosity of the electrolyte, and ensures the rate and low-temperature performance of the battery; when thermal runaway occurs, it can more quickly respond to the battery protection, and the effect of improving the battery safety is more significant. However, the above method has complicated steps. After the microcapsules are prepared, they must be mixed with an isolation membrane protective agent and then coated on the isolation membrane surface. The coated resin on the isolation membrane is prone to pore blockage. In addition, the above method also increases the internal resistance of the isolation membrane, affects the lithium ion transmission, and affects the battery's rate performance and low temperature performance. In the normal cycle of the battery, the metal ions of the positive electrode material will change from low-valent to high-valent when delithiation occurs. The high-valent metal ions are easily reacted with the electrolyte due to their strong reducing properties, thereby causing the battery cycle performance to be reduced and having an adverse effect. Summary of the invention
[0004] In order to better solve the above technical problems, the present invention provides a flame retardant lithium battery positive electrode adhesive and a preparation method thereof.
[0005] In a first aspect, a method for preparing a flame retardant lithium battery positive electrode adhesive comprises the following steps: firstly using an esterified solvent-friendly chain segment, and then preparing a microcapsule adhesive encapsulated with a flame retardant by reversible addition-fragmentation chain transfer polymerization.
[0006] In the present invention, the use of esterified solvent-friendly segments specifically includes the following steps: preparing raw materials according to the following weight parts: 20 to 40 parts of chain transfer agent, 90 to 550 parts of solvent-friendly segments with molecular weights of 1000 to 5000, 20 to 40 parts of dehydrating agent, 1 to 5 parts of catalyst and 500 to 1500 parts of anhydrous dichloromethane; mixing and stirring the above raw materials, concentrating by rotary evaporation, adding to n-hexane to collect polymers through precipitation reaction; re-dissolving and concentrating the polymers in dichloromethane solution, purifying by column, concentrating the eluate, and vacuum drying to obtain yellow powder.
[0007] In the present invention, the 90-550 molecular weight 1000-5000 solvent-philic segment is a 450-550 molecular weight 1000 solvent-philic segment, a 225-275 molecular weight 2000 solvent-philic segment or a 90-110 molecular weight 5000 solvent-philic segment.
[0008] In the present invention, the solvent-philic segment is selected from polyethylene glycol monomethyl ether or polypropylene glycol monomethyl ether.
[0009] In the present invention, the chain transfer agent is selected from 3-(benzylthiothiocarbonylthio) propionic acid (CAS No. 497931-76-7).
[0010] In the present invention, the reversible addition-fragmentation chain transfer polymerization comprises the following steps: 5 to 15 parts of the yellow powder, 20 to 50 parts of nucleating monomers, 0.5 to 2 parts of cross-linking agents, 0.1 to 0.2 parts of azobisisobutyronitrile, 3 to 8 parts of flame retardants, 60 to 180 parts of ethanol and 20 to 40 parts of water are mixed and stirred uniformly, nitrogen is introduced, and the temperature of the sealed container is raised to react and disperse polymerization is performed; and finally, the mixture is dried into powder by a nitrogen spray dryer.
[0011] In the present invention, the nucleating monomer is at least one selected from the group consisting of styrene, methylstyrene, acrylonitrile, methacrylonitrile, methacrylamide, methyl methacrylate and methyl acrylate.
[0012] In the present invention, the crosslinking agent is selected from at least one of divinylbenzene and trimethylolpropane triacrylate.
[0013] In the present invention, the flame retardant is an organic flame retardant. Preferably, the organic flame retardant is at least one selected from triphenyl phosphate, hexaphenoxy cyclotriphosphazene, tetrabromobisphenol A, trichloropropyl phosphate and triphenol phosphate.
[0014] In the present invention, the temperature-raising reaction refers to heating to 60-80° C. and reacting for 7-9 hours.
[0015] In a second aspect, a flame retardant lithium battery positive electrode adhesive is prepared by the above preparation method.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] The present invention first adopts esterified solvent-friendly segments, and then prepares them through reversible addition-fragmentation chain transfer polymerization to obtain a microcapsule adhesive wrapped with a flame retardant. In this way, the flame retardant is wrapped in the positive electrode adhesive microcapsule. At high temperature (>120°C), the trithioester group connecting the solvent-friendly segment and the solvent-phobic segment will be cracked at high temperature, and the amphiphilicity of the microcapsule will be destroyed, thereby releasing the flame retardant for flame retardancy. At the same time, in the normal cycle of the battery, the metal ions of the positive electrode material will change from low-valent to high-valent when delithiation occurs. The trithioester group of the present invention and its cracked product can both be complexed with high-valent metal ions, thereby preventing the reaction between the high-valent metal ions and the electrolyte, and can improve the normal cycle performance of the battery.
[0018] The present invention combines adhesive with flame retardant to reduce the addition of other substances, reduce internal resistance, and avoid the impact of other components; moreover, single-layer coating is only required instead of multi-layer coating on one side, thus reducing processing cost. The selected microcapsules have small particle size (100-200nm), and the number of particles with small particle size is larger under the same mass, which can better improve the bonding force; and the hollow structure can buffer the expansion and rolling of the material to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is an electron microscope image of the microcapsule before encapsulation in Example 1 of the present invention;
[0020] Figure 2 This is an electron microscope image of Example 1 of the present invention after packaging;
[0021] Figure 3 This is an electron microscope image of the microcapsule before encapsulation in Example 2 of the present invention;
[0022] Figure 4 This is an electron microscope image of the microcapsules before encapsulation in Example 3 of the present invention. DETAILED DESCRIPTION
[0023] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0024] Unless otherwise specified, the meanings of the terms in this specification are the same as those generally understood by those skilled in the art. However, if there is any conflict, the definitions in this specification shall prevail.
[0025] As used herein, "includes," "comprising," "including," "containing," "having," or other variations are intended to encompass non-exclusive inclusions, and no distinction is made between these terms. The term "comprising" means that other steps and ingredients that do not affect the end result may be added. The term "comprising" also includes the terms "consisting of" and "consisting essentially of." The compositions and methods / processes of the present invention comprise, consist of, and consist essentially of the essential elements and limitations described herein, as well as any additional or optional ingredients, components, steps, or limitations described herein.
[0026] All numerical values or expressions used in the specification and claims relating to component amounts, process conditions, etc. should be understood to be modified by "about" in all cases. All ranges relating to the same component or property include endpoints, which can be independently combined. Since these ranges are continuous, they include every numerical value between the minimum and maximum values. It should also be understood that any numerical range cited in the application is expected to include all subranges within the range.
[0027] The present invention is further described in detail below with reference to the embodiments.
[0028] Example 1
[0029] A method for preparing a flame retardant lithium battery positive electrode adhesive comprises the following steps:
[0030] Step 1, prepare the following raw materials by weight: 30 parts of 3-(benzylthiocarbonylthio) propionic acid, 500 parts of 1000 molecular weight polyethylene glycol monomethyl ether, 23 parts of a dehydrating agent (dicyclohexylcarbodiimide), 1.3 parts of a catalyst (4-dimethylaminopyridine) and 1000 parts of anhydrous dichloromethane; mix and stir the above raw materials for 24 hours, then concentrate the mixture by rotary evaporation, add it to n-hexane and collect the polymer by precipitation reaction; redissolve and concentrate the polymer in a dichloromethane solution, further purify it by passing it through a silica gel column, then concentrate the eluate, and finally vacuum dry it at 45°C to obtain a yellow powder, the electron microscope image is as shown in Figure 1 As shown;
[0031] Step 2, 10 parts of the yellow powder obtained in step 1, 35 parts of styrene, 1 part of divinylbenzene, 0.15 parts of azobisisobutyronitrile, 5 parts of flame retardant, 100 parts of ethanol and 25 parts of water are mixed and stirred evenly, nitrogen is passed for 30 minutes, the closed container is heated to 70°C and reacted for 8 hours to perform dispersion polymerization; finally, it is dried into powder by a nitrogen spray dryer to obtain a microcapsule adhesive wrapped with a flame retardant, and the electron microscope image is as follows Figure 2 shown.
[0032] Example 2
[0033] A method for preparing a flame retardant lithium battery positive electrode adhesive comprises the following steps:
[0034] Step 1, prepare the following raw materials by weight: 20 parts of 3-(benzylthiocarbonylthio) propionic acid, 550 parts of polypropylene glycol monomethyl ether with a molecular weight of 1000, 20 parts of a dehydrating agent (dicyclohexylcarbodiimide), 5 parts of a catalyst (4-dimethylaminopyridine) and 1000 parts of anhydrous dichloromethane; mix and stir the above raw materials for 24 hours, then concentrate the mixture by rotary evaporation, add it to n-hexane and collect the polymer by precipitation reaction; redissolve and concentrate the polymer in a dichloromethane solution, further purify it by passing it through a silica gel column, then concentrate the eluate, and finally vacuum dry it at 45°C to obtain a yellow powder, the electron microscope image of which is as shown in FIG. Figure 3 As shown;
[0035] Step 2, 15 parts of the yellow powder obtained in step 1, 20 parts of methyl styrene, 2 parts of divinylbenzene, 0.1 parts of azobisisobutyronitrile, 8 parts of flame retardant, 80 parts of ethanol and 20 parts of water are mixed and stirred evenly, nitrogen is passed for 35 minutes, the closed container is heated to 80°C and reacted for 7 hours to perform dispersion polymerization; finally, it is dried into powder by a nitrogen spray dryer to obtain a microcapsule adhesive wrapped with a flame retardant.
[0036] Example 3
[0037] A method for preparing a flame retardant lithium battery positive electrode adhesive comprises the following steps:
[0038] Step 1, prepare the following raw materials by weight: 40 parts of 3-(benzylthiocarbonylthio) propionic acid, 450 parts of polyethylene glycol monomethyl ether with a molecular weight of 1000, 40 parts of a dehydrating agent (dicyclohexylcarbodiimide), 1 part of a catalyst (4-dimethylaminopyridine) and 1000 parts of anhydrous dichloromethane; mix and stir the above raw materials for 24 hours, then concentrate the mixture by rotary evaporation, add it to n-hexane and collect the polymer by precipitation reaction; redissolve and concentrate the polymer in a dichloromethane solution, further purify it by passing it through a silica gel column, then concentrate the eluate, and finally vacuum dry it at 45°C to obtain a yellow powder, the electron microscope image is as shown in Figure 4 As shown;
[0039] Step 2, 5 parts of the yellow powder obtained in step 1, 50 parts of methacrylamide, 0.5 parts of trimethylolpropane triacrylate, 0.2 parts of azobisisobutyronitrile, 3 parts of flame retardant, 180 parts of ethanol and 20 parts of water are mixed and stirred evenly, nitrogen is passed for 25 minutes, the closed container is heated to 60°C and reacted for 9 hours to perform dispersion polymerization; finally, it is dried into powder by a nitrogen spray dryer to obtain a microcapsule adhesive wrapped with a flame retardant.
[0040] Example 4
[0041] The difference from Example 1 is that 500 parts of 1000 molecular weight polyethylene glycol monomethyl ether are replaced by 250 parts of 2000 molecular weight polyethylene glycol monomethyl ether.
[0042] Example 5
[0043] The difference from Example 1 is that 500 parts of 1000 molecular weight polyethylene glycol monomethyl ether are replaced by 100 parts of 5000 molecular weight polyethylene glycol monomethyl ether.
[0044] Comparative Example 1
[0045] A method for preparing a flame retardant lithium battery positive electrode adhesive comprises the following steps:
[0046] (1) After stirring and pre-emulsifying 1.5 parts of 3-(benzylthiothiocarbonylthio) propionic acid, 20 parts of styrene, 1.5 parts of divinylbenzene, 1 part of polyethylene glycol methyl ether methacrylate (molecular weight 2000), 0.4 parts of potassium persulfate, 0.08 parts of polyvinylpyrrolidone PVP-K30 and 150 parts of water in parts by weight, the mixture was added dropwise to 50 parts of water under a nitrogen atmosphere at 70° C. for 2.5 hours, then the mixture was heated to 75° C. and the reaction was continued for 3 hours, and the mixture was cooled to room temperature to obtain a first reactant;
[0047] (2) After stirring and pre-emulsifying 5 parts of styrene, 1.5 parts of isooctyl acrylate, 0.4 parts of potassium persulfate, 0.12 parts of polyvinylpyrrolidone PVP-K30 and 100 parts of water, the pre-emulsified liquid is added dropwise to the first reactant obtained in step (1), and the mixture is added dropwise at 70° C. under a nitrogen atmosphere for 2.5 hours, and then the temperature is raised to 75° C. and the reaction is continued for 3 hours to obtain a second reactant, and the second reactant is then spray-dried.
[0048] Test Comparison
[0049] Examples 1-5 and Comparative Example 1 were added to methyl pyrrolidone to prepare an adhesive with a solid content of 7%, and named Samples 1 to 6 in sequence; slurry was prepared: 28 parts of methyl pyrrolidone (NMP) were added to a double planetary mixer, 1 part of conductive carbon Super.P, 0.5 parts of conductive graphite KS-6 were added, stirred for 1 hour, 45 parts of the sample were added, stirred for 1.5 hours, 100 parts of DY-3 active material were added, stirred for 30 minutes, and then discharged, scraped on the carbon-coated foil, and baked at 100°C for 1 minute to obtain a positive electrode sheet. The positive electrode sheet was then subjected to a bidirectional bending test and a bulging combustion test, and the test data are shown in Table 1 below.
[0050] Preparation of negative electrode sheet: negative electrode materials graphite, conductive carbon black, sodium carboxymethyl cellulose and styrene butadiene latex are mixed in a mass ratio of 94.5:1:2.25:2.25, deionized water is added to obtain negative electrode slurry, and then the negative electrode slurry is scraped on the surface of copper foil and dried to obtain a negative electrode sheet;
[0051] Bulging combustion is an experiment after assembling the battery. Preparation of lithium-ion battery: Assemble the above-mentioned positive electrode sheet, negative electrode sheet, electrolyte and separator to obtain a lithium-ion battery.
[0052]
[0053] The flame retardant lithium battery positive electrode adhesive based on microcapsule materials of samples 1-5 has the following structural advantages compared with the lithium battery positive electrode adhesive of spherical micron materials of sample 6: ① Particle morphology. Spherical materials are more commonly used. The present invention is a microcapsule morphology (such as Figure 1 , 3 4, the size of the microcapsule is 100-200nm, and some microcapsules collapse when dried, which also partially shows that it has a certain effect of alleviating volume expansion). During the polymerization process, the flame retardant in the system can be wrapped in the particles, while the spherical particles cannot be wrapped, and the inhibitor is blown away during the spray drying process, resulting in non-flame retardant; ② Particle size, currently more micron-level spherical adhesives are used, and the microcapsule material used in the present invention has a smaller particle size and is hollow (such as Figure 1As shown, 100-200nm), the number of particles can be significantly increased under the same mass, so that the particles can better bond with the active substance and the conductive substance to enhance the adhesion; ③ polymer structure, now more is a random copolymer structure, the hard monomer solvent-phobic segment polystyrene and the soft monomer solvent-philic segment polyethylene glycol monomethyl ether are irregularly distributed on the polymer chain, and the present invention uses a block copolymer structure. Through the selection of monomers, the hard monomer can be designed in the core and the soft monomer on the surface of the particle, which is beneficial to improve the adhesion; ④ when designing, a trithioester type chain transfer agent is selected, and its Z group side has an esterifiable carboxyl group, which can separate the solvent-philic segment from the solvent-phobic segment. The chain transfer agent will automatically decompose at high temperature (above 120°C), thereby causing the solvent-philic segment of the particle to be disconnected from the solvent-phobic segment, the amphiphilicity disappears, and the particle cannot maintain the microcapsule morphology, thereby releasing the encapsulated flame retardant to achieve a flame retardant effect.
[0054] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. A method for preparing a flame retardant lithium battery positive electrode adhesive, characterized in that: It includes the following steps: Firstly, the microcapsule adhesive encapsulated with the flame retardant is prepared by using an esterified solvent-friendly chain segment and then by reversible addition-fragmentation chain transfer polymerization; The method of using the esterified solvent-friendly chain segment specifically comprises the following steps: preparing the following raw materials in parts by weight: 20-40 parts of a chain transfer agent, 90-550 parts of a solvent-friendly chain segment with a molecular weight of 1000-5000, 20-40 parts of a dehydrating agent, 1-5 parts of a catalyst and 500-1500 parts of anhydrous dichloromethane; mixing and stirring the above raw materials, concentrating them by rotary evaporation, adding them to n-hexane to collect the polymer through precipitation reaction; re-dissolving and concentrating the polymer in a dichloromethane solution, purifying it by column, concentrating the eluate, and vacuum drying it to obtain a yellow powder; The solvent-philic segment is selected from polyethylene glycol monomethyl ether or polypropylene glycol monomethyl ether; The chain transfer agent is selected from 3-(benzylthiothiocarbonylthio) propionic acid; The reversible addition-fragmentation chain transfer polymerization comprises the following steps: 5 to 15 parts of the yellow powder, 20 to 50 parts of a nucleating monomer, 0.5 to 2 parts of a cross-linking agent, 0.1 to 0.2 parts of azobisisobutyronitrile, 3 to 8 parts of a flame retardant, 60 to 180 parts of ethanol and 20 to 40 parts of water are mixed and stirred evenly, nitrogen is introduced, and a closed container is heated to react and disperse polymerization is performed; and finally, the mixture is dried into powder by a nitrogen spray dryer.
2. The method for preparing a flame retardant lithium battery positive electrode adhesive according to claim 1, characterized in that: The 90-550 molecular weight 1000-5000 solvent-philic segment is a 450-550 molecular weight 1000 solvent-philic segment, a 225-275 molecular weight 2000 solvent-philic segment or a 90-110 molecular weight 5000 solvent-philic segment.
3. The method for preparing a flame retardant lithium battery positive electrode adhesive according to claim 1, characterized in that: The flame retardant is an organic flame retardant.
4. The method for preparing a flame retardant lithium battery positive electrode adhesive according to claim 1, characterized in that: The nucleating monomer is selected from at least one of styrene, methylstyrene, acrylonitrile, methacrylonitrile, methacrylamide, methyl methacrylate and methyl acrylate.
5. The method for preparing a flame retardant lithium battery positive electrode adhesive according to claim 1, characterized in that: The temperature-raising reaction refers to heating the temperature to 60-80° C. and reacting for 7-9 hours.
6. A flame retardant lithium battery positive electrode adhesive, characterized in that: The compound is prepared by the preparation method described in any one of claims 1 to 5.
Citation Information
Patent Citations
Method for enhancing safety of lithium-ion battery
CN105742733A
Flame-retardant composite diaphragm, preparation method thereof and lithium ion battery
CN113078412A
Binder material for improving low-temperature performance of lithium battery and preparation method of binder material
CN113644266A